2016
DOI: 10.5350/dajpn2016290102
|View full text |Cite
|
Sign up to set email alerts
|

Dokuz Tip Mizaç Modeli’nin kişilik bozukluklarıyla ilişkisi

Abstract: Relation of the Nine Types of Temperament Model with personality disordersObjective: Aim of this study is to determine the correspondence between personality categories and the types making up the Nine Types of Temperament Model (NTTM) -a new temperament model which evaluates personality disorders within the context of temperament traits and maladaptive personality features-and conceptualization of NTTM types. Method:The sample group is composed of 117 participants with a personality disorder. SCID II and Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Limited research has examined the utility of interventions targeting resilience to prevent or treat substance use, specifically smoking or nicotine dependence. Although there is some controversy regarding whether resilience is a personality trait or a characteristic amenable to intervention (Yilmaz, Unal, Gencer, Aydemir, & Selcuk, 2015), some research indicates the promise of intervening on resilience. For example, some intervention research has shown that attempts to increase resilience in young adults have been effective in not only increasing resilience but also increasing coping skills and protective factors (e.g., positive affect, selfesteem) and decreasing symptoms of depression, stress, and negative affect (Steinhardt & Dolbier, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has examined the utility of interventions targeting resilience to prevent or treat substance use, specifically smoking or nicotine dependence. Although there is some controversy regarding whether resilience is a personality trait or a characteristic amenable to intervention (Yilmaz, Unal, Gencer, Aydemir, & Selcuk, 2015), some research indicates the promise of intervening on resilience. For example, some intervention research has shown that attempts to increase resilience in young adults have been effective in not only increasing resilience but also increasing coping skills and protective factors (e.g., positive affect, selfesteem) and decreasing symptoms of depression, stress, and negative affect (Steinhardt & Dolbier, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It could be said that the personality traits of Type 2 temperament include the qualities required by the teaching profession: twos are emotional, sincere, outgoing, loving, selfsacrificing, helpful, generous individuals who are able to have contact and communication easily and have strong social relationships (Selçuk&Yılmaz, 2015). Type 5 individuals who were high in number in our study tend to have withdrawn, quiet, shy, analytic, isolated, observer, rationalist, abstractive, distant, objective, investigative and reasonable personalities (Yılmaz et al, 2014b). Considering all the above listed characteristics, it can be asserted that the Type 5 temperament that is common among the students attending the pedagogical formation program in physical education appears to have a week connection and relationship with the profession of teaching.…”
Section: Tablementioning
confidence: 53%
“…2) Another remarkable finding is that while general teaching effect had no impact on professional attitudes in any of the temperament types, the general teaching effect perceptions of the participants with Type 2 temperament had a predictive effect on their professional attitudes. This can be interpreted in association with the qualities possessed by individuals with Type 2 temperament, which is defined by such qualities as being emotional, sincere, outgoing, able to have contact and communication easily, loving, self-sacrificing, helpful, generous and strong in social relationships (Yılmaz et al, 2014b). The fact that this temperament type involving emotional and sensitive characteristics in connection with social relationships is affected by general teaching efficacy that represents extrinsic factors can be a mediator in the reflection of the factors other than teachers' self-efficacy on their professional attitudes.…”
Section: Tablementioning
confidence: 99%
“…Part of what can cause confusion in the abstraction of social identity for novice researchers is that often social structures in which identities play out are perceived as relatively fixed (Burke, 1980), and the aspects that contribute to social identities themselves are sometimes static (Yilmaz, Unal, Gencer, Aydemir, & Selcuk, 2015). Author DJ reflects on her public school education as a child, being taught that identity is rigidyou are a boy or a girl, you may be attracted to either boys or girls, you were born with XX sex chromosomes so you are a girl, you are born in Canada and therefore you are Canadian.…”
Section: Addressing the Complexities Of Positionalitymentioning
confidence: 99%